Road pricing theory and practice - Lewis, Nigel C. (Thomas Telford, 1993)
This book describes the theory and practice of congestion charging using advanced electronic systems. The general principles and potential benefits are presented and a framework for good practice established. The financial, institutional, technological and social issues that must be addressed are outlined and a comparitive assessment and review of current and pilot projects in Europe and South-East Asia are given.